(untitled) (Third Sector Social Economic Review, 2023)
The aim of this study is to explain the predictive effects of organizational conflict management and organizational silence levels on organizational citizenship behavior in educational institutions. The research sample consisted of 500 teachers working in kindergarten, primary school, secondary school and high school in Uşak city center and determined by stratified random sampling method. Data were collected with the Organizational Conflict Management Styles Scale, the Organizational Silence Scale, and the Organizational Citizenship Behavior Scale. In the analysis of the data, descriptive statistics such as arithmetic mean and standard deviation were calculated, and hierarchical regression analysis was performed in the predictive analysis. Findings showed that school administrators used the conflict management styles integrating, compromising, conforming and avoiding at a low level, and using the dominating style at a high level. In addition, the averages calculated for the variables of organizational silence and organizational citizenship behaviors showed that teachers showed moderate organizational silence; indicated that they exhibited high levels of organizational citizenship behaviors. The hierarchical regression results, on the other hand, showed that the ""domination"" strategy, one of the conflict management methods, was a negative predictor of organizational citizenship behavior in the first stage of the regression. However, in the second stage of the analysis, it was seen that the sub-dimensions of ""school environment, source of silence and administrator"", which are among the dimensions of organizational silence, are a negative predictor of organizational citizenship behavior. In the context of the results obtained, it can be suggested that school administrators try to use conciliatory and integrative conflict management styles as much as possible and examine the factors that cause organizational silence in educational organizations in depth.